Pemahaman Bonum Commune Dalam Filsafat Cina - Benny Suwito (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
Chinese philosophy, specifically Confucianism gave color to the lives of Chinese people in Indonesia. This paper will try to describe the teachings of Confucius in pursuing the bonum commune through the main principle “zheng ming” （证明） as a basis for achieving that. However, in explaining this main principle, this paper will try to explore the concept of “datong” as a concept of harmony dreamed of by Confucius, and after that the author will explain some concepts that need to be possessed in order to materialize. Finally, this paper will reflect on how filial piety played as the key to the realization of “zheng ming” in building a harmonious society (datong) in Indonesia